Study of Settlement of Industrial Relation Disputes through Mediation - Widya Novrianna,; Bonaventura Ngarawula,; Budhy Prianto, (International Journal of Research in Social Science and Humanities (IJRSS) ISSN:2582-6220, DOI: 10.47505/IJRSS, 2022)
This study aims to analyze the implementation of industrial relations dispute resolution policies through mediation in East Kutai Regency, as well as to describe and analyze the supports and obstacles in the performance of these policies. This study uses a descriptive qualitative method based on the implementation model of George Edward III with indicators of communication, resources, disposition, and bureaucratic structure. Data collection techniques using interviews, observation, and documentation. Then the data analysis technique used is the interactive analysis model from Miles and Huberman. The study results indicate that the implementation of industrial relations dispute resolution policies through mediation, commonly called industrial relations mediation, in the East Kutai Regency, has been run by applicable regulations. The expertise of industrial relations mediators in resolving disputes is the main thing in supporting the successful implementation of this policy. Current technological developments also provide convenience for implementers so that the industrial relations mediation mechanism becomes more efficient. However, of course, there are obstacles to the implementation of industrial relations mediation policies, including the lack of industrial relations mediators, the unavailability of a particular mediation room, mediators who double as structural officials,